The Railway children - Nesbit, Edit (Leicestershire, UK : Ladybird Books, 1984)
The children loved their new life in the little house beside the railway. They made friends with the Station Master and the Porter, and gave special names to all the trains. Only one thing spoiled it. Why didn't Father come back to them?
Keywords: Children's Stories; Family's - Fiction